Pembebasan Bersyarat Bagi Narapidana Di Lembaga Pemasyarakatan Klas II B Lubuk Pakam - Situmorang, Edward Pahala; Barus, Utary Maharany; Isnaini, Isnaini (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
This study aims to look at the implementation of imprisonment for prisoners and how the implementation of parole for prisoners as well as what are the obstacles and efforts in the implementation of parole for prisoners. The method of approach used in this research is normative juridical, which is an approach that emphasizes searches and library materials. Conditional release is the process of fostering prisoners outside Penitentiary after undergoing at least 2/3 of his sentence with a stipulation of 2/3 of the criminal period of at least 9 months. Obstacles that occur in the Conditional Release by the Class II Correctional Institution B Lubuk Pakamadalah Tightening parole for prisoners related to Government Regulation Number 99 of 2012 contrary to Law Number 12 of 1995 as stated that each prisoner is entitled to the same treatment as the right to obtain parole.